The Effectiveness of Implementing the Inside-Outside Circle Cooperative Learning Model on Social Skills and Conceptual Understanding of Science in Elementary Schools - Fitriana, Allysha Syatifa; Ali, Aisyah Mohd; Hui, Tan Jia (Journal Sains and Education, 2025)
This study aims to analyze the effectiveness of implementing the Inside-Outside Circle (IOC) cooperative learning model on social skills and understanding of science concepts at the elementary school level. The IOC model encourages student interaction through a method of moving and discussing in groups, which can enhance communication, collaboration, and understanding of the material. The approach used is a literature study, analyzing previous research findings related to the application of the IOC model in learning. The analysis results indicate that the application of the IOC model is effective in improving students' social skills, such as communication, teamwork, and sharing understanding with classmates. This model also successfully enhances students' understanding of science concepts through engaging and collaborative discussion activities. However, the IOC model faces challenges such as time management and limitations of classroom facilities, which may impact its implementation. Therefore, proper planning, teacher training, and the provision of supporting resources and facilities are essential for the success of this model. Overall, the implementation of the Inside-Outside Circle learning model holds significant potential to improve the quality of education at the elementary school level, particularly in developing social skills and understanding science concepts, with special attention to the practical aspects that need to be adapted in the field